IMPACT OF COVID-19 ON OUTCOMES OF PATIENTS WITH HEMATOLOGIC MALIGNANCIES: A MULTI-CENTER, RETROSPECTIVE STUDY - İbrahim Halil Açar; Sebnem Izmir Güner; Muzeyyen Aslaner Ak; Mesut Gocer; Erman Ozturk; Figen Atalay; Gulden Sincan; Aysun Senturk Yikilmaz; Omer Ekinci; Idris Ince; Emine Gulturk; Nazli Demir; et al. (Mediterranean Journal of Hematology and Infectious Diseases, 2022)
Objectives: Patients with hematologic malignancies have a high risk of coronavirus disease 2019 (COVID-19) mortality. This study aimed to investigate the impact of COVID-19 on mortality rates in patients with various hematologic malignancies and to determine risk factors associated with all-cause mortality.